2018
DOI: 10.1038/s41419-018-0825-1
|View full text |Cite
|
Sign up to set email alerts
|

Potent effect of the MDM2 inhibitor AMG232 on suppression of glioblastoma stem cells

Abstract: Testing new ways to identify untapped opportunities for glioblastoma therapies remains highly significant. Amplification and overexpression of MDM2 gene is frequent in glioblastoma and disrupting the MDM2−p53 interaction is a promising strategy to treat the cancer. RG7112 is the first-in class inhibitor and recently discovered AMG232 is the most potent MDM2 inhibitor known to date. Here, we compared the effects of these two clinical MDM2 inhibitors in six glioblastoma cell lines and ten patient-derived gliobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 48 publications
(41 reference statements)
4
42
0
Order By: Relevance
“…Thus, an intact p53-ZEB1 feedback loop represents an important regulatory mechanism for epithelial phenotype maintenance, suppression of metastasis, and protection against enhanced chemoresistance. Importantly, two independent studies with MDM2 inhibitors, which both reactivated p53 and downregulated ZEB1, also documented decreased stemness features and glioblastoma aggressiveness (Giacomelli et al, 2017;Her et al, 2018). Such effects of p53 reactivation on ZEB1 may be mediated via activation of microRNAs that p53 can activate such as miR-34, miR-145, and miR-200 (Chang et al, 2011;Siemens et al, 2011;Ren D. et al, 2013).…”
Section: Interplay Between Micrornas Zeb1 and Dna Damage Responsementioning
confidence: 96%
“…Thus, an intact p53-ZEB1 feedback loop represents an important regulatory mechanism for epithelial phenotype maintenance, suppression of metastasis, and protection against enhanced chemoresistance. Importantly, two independent studies with MDM2 inhibitors, which both reactivated p53 and downregulated ZEB1, also documented decreased stemness features and glioblastoma aggressiveness (Giacomelli et al, 2017;Her et al, 2018). Such effects of p53 reactivation on ZEB1 may be mediated via activation of microRNAs that p53 can activate such as miR-34, miR-145, and miR-200 (Chang et al, 2011;Siemens et al, 2011;Ren D. et al, 2013).…”
Section: Interplay Between Micrornas Zeb1 and Dna Damage Responsementioning
confidence: 96%
“…AMG232 effects were tested in the therapy resistant and putative tumor initiating GBM stem cells. AMG232 exhibited relative selectivity to wt-p53 stem cells was very efficacious in inhibiting three-dimensional tumor spheroids growth and stemness-related factors [ 116 ]. Another study found that nutlin3a-mediated inhibition of MDM2/p53 interaction and led to an impairment in DNA repair that correlated with potentiation of temozolomide-mediated cell death both in vitro and in vivo in GBM [ 45 ].…”
Section: P53-targeted Therapiesmentioning
confidence: 99%
“…However, they suffer from the caveat that canonical ubiquitination of p53 mutants is MDM2independent (355). An interesting example is AMG-232 (KRT-232) which averaged IC 50 s in the low nanomolar range in GBM cell lines and patient-derived GBM stem cells (356). More importantly, AMG-232's suppressive effects seemed to extend selectively to GBM stem cells as the compound displayed efficacious inhibition of stemness-related factors Nestin and ZEB1 in a spheroid culture model.…”
Section: Therapeutic Targeting Of E3 Ubiquitin Ligasesmentioning
confidence: 99%